Industrial concentration and inflation - Lustgarten, Steven (Washington : American Enterprise Institute for Public Policy Research, 1975)
The book examines the claim that industry concentration is an important source of inflation. The author analyses the theory and the accumulated evidence that relate the fewness of sellers in certain manufacturing industries to the rate of economy-wide inflation, finding the theory subject to major criticism and the empirical evidence highly ambiguous.
Includes bibliographical references.
lje 4/25/17
Loans
Keywords: Inflation (Finance); Industrial concentration